2015
DOI: 10.1016/j.devcel.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Unfolded Protein Response Contributes to the Control of Cortical Neurogenesis

Abstract: The cerebral cortex contains layers of neurons sequentially generated by distinct lineage-related progenitors. At the onset of corticogenesis, the first-born progenitors are apical progenitors (APs), whose asymmetric division gives birth directly to neurons. Later, they switch to indirect neurogenesis by generating intermediate progenitors (IPs), which give rise to projection neurons of all cortical layers. While a direct lineage relationship between APs and IPs has been established, the molecular mechanism th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
212
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(231 citation statements)
references
References 69 publications
16
212
3
Order By: Relevance
“…Furthermore, ALS is marked by mitochondrial dysfunction (61). Recent work has revealed that in the absence of Elp3 in mice, cortical neurogenesis is impaired because of the activation of the unfolded protein response, which is triggered by stress in the endoplasmic reticulum (9). That study and ours help elucidate the function of the Elongator complex in neurons and reveal that its absence triggers intracellular stress.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Furthermore, ALS is marked by mitochondrial dysfunction (61). Recent work has revealed that in the absence of Elp3 in mice, cortical neurogenesis is impaired because of the activation of the unfolded protein response, which is triggered by stress in the endoplasmic reticulum (9). That study and ours help elucidate the function of the Elongator complex in neurons and reveal that its absence triggers intracellular stress.…”
Section: Discussionmentioning
confidence: 65%
“…The C terminus of IKAP/ELP1 has been shown to bind c-Jun N-terminal kinase (JNK) and to regulate JNK cytosolic stress signaling (12). Loss of Elp3 in mouse cortical neurons triggers endoplasmic reticulum stress (9), and Elp3 deletion in yeast causes disruptions in mitochondrial function (10). ELP3 has been demonstrated to localize in mitochondria in HeLa cells, mouse brain, and Toxoplasma (13,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2G; P=0.0001). The impaired IPC development observed in Nfix −/− mice could potentially occur as a result of increased direct neurogenesis from radial glia, similar to that observed in Elp3 conditional knockout mice (Laguesse et al, 2015). To determine whether this was the case we performed a 48 h BrdU chase experiment (labeling with BrdU from E13.5).…”
Section: Tbr2mentioning
confidence: 99%